Modeling plastics injection molding operation using simulation - Li Mei, Tan (2014)
Capacity planning plays a key role in the overall performance of an industries business and it is the new challenges for Malaysia manufacturing ﬁrms to maintain and practice it. In this study, a long series of discuss about the capacity planning in plastic injection molding operation using arena simulation software. Simulation as a decision making tool to evaluate the capacity utilization in term of Worker and material use in the operation. Simulation tool simulate the current facility and to analyze and evaluate the operation’s performance and determines the real factors measures to be undertaken in future to improve the efﬁciency of the plastic injection molding plant. The factors comprise the insufﬁcient utilize of manpower, machines, and materials cause the running production slow and delay time for shipping ﬁnished goods to customers. Model will be developed in simulation software as same as real operation and test run to identiﬁes the problems. Try-and-error to increase or decrease capacity of materials in duration of working time to the model will be tested several times in order to determine an improvement to enhance the operation. What-if analysis and scenario planning will be discussed by referring to the improvement model to identify the impact and provide better solution for future improvement